The protection of cultural heritage sites from geo-hazards: The PROTHEGO project - Themistocleous, Kyriacos; Cuca, Branka; Agapiou, Athos; Lysandrou, Vasiliki; Tzouvaras, Marios; Hadjimitsis, Diofantos G.; Kyriakidis, Phaedon; Kouhartsiouk, Demetris; Margottini, Claudio; Spizzichino, Daniele; Cigna, Francesca; Crosta, Giovanni; et al. (My University, 2016)
Examining natural hazards responsible for cultural heritage damages all over Europe, especially over large or remote areas is extremely difficult, expensive and time consuming. There is a need identify and respond to natural hazards before they create irreparable damage to cultural heritage sites. The PROTHEGO project uses radar interferometry to monitor surface deformation with mm precision to analyze the impact of geo-hazards in cultural heritage sites in Europe. The project applies novel InSAR techniques to monitor monuments and sites that are potentially unstable due to landslides, sinkholes, settlement, subsidence, active tectonics as well as structural deformation, all of which could be affected of climate change and human interaction. To magnify the impact of the project, the approach will be implemented in more than 400 sites on the UNESCO World Heritage List (WHL) in geographical Europe. After the remote sensing investigation, detailed geological interpretation, hazard analysis, localscale monitoring, advanced modelling and field surveying for the most critical sites will be carried out to discover the cause and extent of the observed motions. PROTHEGO (PROTection of European Cultural HEritage from GeO-hazards) is a collaborative research project funded in the framework of the Joint Programming Initiative on Cultural Heritage and Global Change (JPICH) – Heritage Plus in 2015–2018.
Keywords: Cultural heritage; Geo-harzards; InSAR; UNESCO